SOCIAL SUPPORT, PSYCHOLOGICAL RESILIENCE, AND QUALITY OF LIFE AMONG TUBERCULOSIS PATIENTS - Atika Yolanda Silaban; Yusnilawati; Yuliana; Indah Mawarti; Febri Tri Andini (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Tuberculosis remains a major public health challenge in Indonesia, with psychosocial factors potentially influencing patients’ quality of life during treatment. This quantitative correlational study with a cross-sectional design examined the relationship between social support, psychological resilience, and quality of life among 35 Tuberculosis patients at Kenali Besar Public Health Center, Jambi City, from November 2025 to February 2026 using total sampling. Data were collected using the MSPSS, CD-RISC-25, and WHOQOL-BREF questionnaires and analyzed with Spearman Rank tests. Most respondents were male (60.0%), aged 46–55 years (22.9%), had completed high school (60,0%), and reported high social support, psychological resilience, and quality of life (85.7% each). Social support was positively associated with quality of life (r = 0.611, p < 0.001), while psychological resilience showed an even stronger positive relationship (r = 0.761, p < 0.001). Strengthening both factors may improve quality of life and should be integrated into Tuberculosis management programs.